Thermal Conversion of Coral Waste and its Utilization as Low-Cost Catalyst for Biodiesel Production - Azlan bin Kamari (Tanjung Malim, 2024)
Thermal Conversion of Coral Waste and its Utilization as Low-Cost Catalyst for Biodiesel Production by Azlan bin Kamari